Penerapan Algoritma Apriori Untuk Rekomendasi Display Produk Mebel Furnitur - Rizki Fauzan Suswandy Suswandy; Iwan Rizal Setiawan (Elkom : Jurnal Elektronika dan Komputer, 2022)
In a business , the ability to process data is very necessary, information obtained from a business can provide benefits in an effective and efficient business strategy, but with the development of online business strategy information, some users, in business furniture products are confused choosing product according to the wishes of the buyer Therefore, research is made with the aim of making it easier for users, especially in the field of furniture product business to determine the desired product by implementing a recommendation system on the furniture store website which is taken from the amount of data, this data can be in the form of databases. this is also beneficial for shop owners because with this recommendation system it can help as a means of promoting products that are not selling well. the recommendation system uses the a priori algorithm method with data mining techniques, namely association rules.